The Causes and Outcomes of Early Relaparotomy Following Pediatric Living Donor Liver Transplantation. Issue 7 (27th May 2019) - Okada, Noriki; Sanada, Yukihiro; Onishi, Yasuharu; Urahashi, Taizen; Ihara, Yoshiyuki; Yamada, Naoya; Hirata, Yuta; Katano, Takumi; Imai, Toshimi; Ushijima, Kentaro; Ogaki, Keiko; Otomo, Shinya; et al.
Abstract : Early relaparotomy of adult recipients after living donor liver transplantation (LDLT) is significantly associated with poor prognosis. However, there are few reports focusing on pediatric recipients after LDLT. The aim of this study is to clarify the causes and outcomes of early relaparotomy after pediatric LDLT. A total of 265 pediatric recipients (272 LDLTs) transplanted from May 2001 to October 2015 were retrospectively analyzed. Early relaparotomy was defined as surgical intervention performed within 3 months after LDLT. Early relaparotomy was performed 49 times for 33 recipients (12.5%). The recipient and graft survival rates in the early relaparotomy group were significantly lower than those in the nonearly relaparotomy group, respectively (75.0% and 63.6% versus 96.6% and 95.8%; both P  < 0.001). Left lateral segment grafts were used significantly more frequently in the nonrelaparotomy group ( P  = 0.01). According to the multivariate analysis, the preoperative Pediatric End‐Stage Liver Disease (PELD)/Model for End‐Stage Liver Disease (MELD) score of the early relaparotomy group was significantly higher than that of the nonearly relaparotomy group (13.7 versus 6.3; P  = 0.04). According to the receiver operating characteristic curve, the preoperative PELD/MELD score cutoff point was 17.2. Early relaparotomy due to infectious causes led to significantly poorer graft survival than that due to noninfectious causes ( P  = 0.04). In conclusion, the recipient and graft survival rates of the early relaparotomy group were significantly lower than those of the nonearly relaparotomy group. A high preoperative PELD/MELD score was a risk factor for early relaparotomy. In particular, early relaparotomy due to infection showed a poor prognosis.